Sheol, the tomb, and the problem of postmortem existence - Suriano, Matthew J. (The journal of Hebrew scriptures, 2016)
The Hebrew Bible often portrays Sheol in a manner evocative of the tomb. In texts such as Psalm 88 the tomb is a dreary and isolating symbol. Yet this contrasts with the positive role of the family tomb where the dead are reunited with their ancestors. The ritual analysis of Judahite bench tombs, however, reveals a dynamic concept of death. This suggests that the varying images of the tomb in biblical literature were not contradictory, but reflective of a process of dying that began with burial.